Perbandingan Peraturan Kode Etik Hakim di Indonesia, Malaysia dan Singapura - Ayunigtyas Putri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Violations of judicial ethics have a negative impact on public trust in the judiciary, making strengthening ethical oversight a key requirement in a modern judicial system. This study compares the regulation and implementation of judicial codes of ethics in Indonesia, Malaysia and Singapore using normative legal research methods with a comparative legal approach. The analysis is descriptivecomparative to assess the effectiveness of regulations and oversight practices. The results show that Indonesia has relatively comprehensive ethical regulations but still faces implementation challenges. Malaysia emphasizes internal oversight with limited transparency, while Singapore implements integrated ethical oversight. This study provides a scientific contribution by offering an evaluation framework for ethical oversight that can serve as a reference for judicial reform at the national and international levels, while emphasizing the importance of consistent oversight and strengthening the internalization of judicial ethics.